Assessing information security performance of enterprise internal financial sharing in cloud computing environment using analytic hierarchy process. (14th July 2022) - Zhou, Xiuying; Weng, Huaqun
The present work aims to improve the efficiency of enterprises by solving a series of problems such as high financial costs, low financial management efficiency and structural redundancy. The maturity model subdivides the four indicators: information security strategy, information security technology, information security organisation and information security operation. An information security evaluation system is constructed for financial sharing. Analytic Hierarchy Process (AHP) and Fuzzy Comprehensive Evaluation (FCE) are combined to evaluate financial sharing capabilities in protecting information security. The proposed model is validated using example data. Results demonstrate that cloud computing-based financial sharing management can effectively reduce financial costs and improve the financial management efficiency of enterprises. The AHP-based model for evaluating information security performances can effectively protect financial information and guarantee enterprises' financial information security. Through experiments, significant and practical references can be provided for promoting the development of large enterprises.